2020
DOI: 10.3390/su13010012
|View full text |Cite
|
Sign up to set email alerts
|

Green and Sustainable Public Procurement—An Instrument for Nudging Consumer Behavior. A Case Study on Romanian Green Public Agriculture across Different Sectors of Activity

Abstract: Green Public Procurement (GPP) became an efficient instrument to achieve the objectives of environmental policy expressed by the European Commission in its Communications. At the same time, it must be addressed by the public authorities as a complex process, in which all purchased goods and services must integrate perfectly into an entire puzzle-like system of legislation, the construction field, innovation, healthcare, food, and education. Scientific references published in the Web of Science (WoS) mainly bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 65 publications
(154 reference statements)
0
9
0
Order By: Relevance
“…The logic of cooperation and mutual benefits to the market and to the public procurer can drive substantial changes in the supply chain (e.g., improve management practices, optimize costs, reduce food waste) and create significant opportunities to optimize innovation mechanisms in the procurement approach (Amann et al, 2014; Bucea‐Manea‐tonis et al, 2021; Soldi, 2018). However, to achieve this, it is necessary to facilitate rules and procedures, strengthen the training of teams and procurement managers, and avoid the administrative burden and potential financial constraints (e.g., higher cost of meals co‐shared with the families), as well as other problems related with the ‘local trap’(Born & Purcell, 2006; Sonnino, 2010).…”
Section: Public Procurement In Portuguese Schools: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The logic of cooperation and mutual benefits to the market and to the public procurer can drive substantial changes in the supply chain (e.g., improve management practices, optimize costs, reduce food waste) and create significant opportunities to optimize innovation mechanisms in the procurement approach (Amann et al, 2014; Bucea‐Manea‐tonis et al, 2021; Soldi, 2018). However, to achieve this, it is necessary to facilitate rules and procedures, strengthen the training of teams and procurement managers, and avoid the administrative burden and potential financial constraints (e.g., higher cost of meals co‐shared with the families), as well as other problems related with the ‘local trap’(Born & Purcell, 2006; Sonnino, 2010).…”
Section: Public Procurement In Portuguese Schools: Resultsmentioning
confidence: 99%
“…These problems were at the root of an increasing number of initiatives across Europe that are driving innovative experiments motivated by environmental, economic, health, well‐being, and social values. These initiatives create new insights into supply chain management, business models, and organizational frameworks of food governance, within an holistic approach (Amann et al, 2014; Bucea‐Manea‐tonis et al, 2021; Morgan, 2008; Soldi, 2018; Sonnino, 2019). Recent literature on this topic focuses on regional or national levels, embracing a single‐country perspective (Cerutti et al, 2016; Galli et al, 2014; Lehtinen, 2012; Testa et al, 2012), or adopts a multi‐country perspective comparing the criteria used within EU countries for public purchasing of food products and catering services (Brammer & Walker, 2011; Neto & Caldas, 2018; Soldi, 2018).…”
Section: State and Public Policies Towards More Sustainable Societies...mentioning
confidence: 99%
“…Using descriptive statistics and semantic similarities (for example the keyword Eastern Europe includes Eastern EU countries, Eastern European countries, and also individually taken countries which are located in those areas, such as Romania, Bulgaria, and Poland; the resources management keyword also comprises foodrelated resources, such as fresh water, fertilisers, and oil), the combination of one or two terms plus the time horizon were kept in mind (publishing year; decade-based range, very important for the trends generation), some examples being presented in Table 1. The systematic literature review revealed that misconceptions accompanying us during the first stage of this research suffered change, faced with the number of interesting documents finally found, a visible signal that the need for the understanding of concepts such as food waste, circular economy, and waste management in Eastern European countries started years ago, increased significantly from 2015, and remains an on-going process due to the specificity of the region and driven by COVID-19 dynamics [46][47][48][49]. The highest share of expenditures on food in 2020 belonged to Eastern European countries: Romania (26.4%), followed by Lithuania (21.7%), Estonia (21.6%), and Croatia (21.4%), whereas the lowest rates belonged to Luxembourg (9.5%), Ireland (9.8%), and Switzerland (9.7%) [50][51][52][53].…”
Section: Methodsmentioning
confidence: 99%
“…However, current business conditions on the market impose the need for constant adjustment and a continual search for ways to raise competitiveness for companies. This is precisely because of the overproduction and oversaturation of the market [11][12][13]. Consequently, companies find it challenging to differentiate and position themselves in consumers' minds (i.e., market positioning).…”
Section: Background Researchmentioning
confidence: 99%